KEBIJAKAN PENANGGULANGAN MASALAH OVER KAPASITAS PADA LEMBAGA KEMASYARAKATAN - Immanuel Yoan; Amad Sudiro (Jurnal Hukum Adigama, 2022)
There is still a lot of overcapacity that occurs in social institutions in Indonesia because, there areseveral criminal cases that should be mediated, but still proceed to the court level. The author wants toraise the issue of how the current overcapacity management policy is and what is the ideal policy toovercome overcapacity in the future. The research method used is normative research. Based on theauthor's analysis of overcapacity prevention policies at this time still tend to prioritize imprisonment,even though there are other alternatives to resolve criminal cases that are classified as minor, namelyRestorative justice, the basic principle of Restorative Justice is mediation. The author concludes thatnot all criminal cases must be resolved with imprisonment, there are other alternatives that can makethe Community Institution less overcapacity, namely restorative justice. It is preferable that theresolution of this overcapacity problem should focus on the process before the entry of these "problematic people" into the correctional facility, namely at the stage of investigation in the police,prosecution at the prosecutor's of ice, up to the stage of court decisions.